Assessment of Pharmacists' Knowledge, Attitude, and Practice on Drugs Disposal in a Sample of Iraqi Community Pharmacists: A Cross-Sectional Study - Abd-ul Munaf Mohammed ,; Al-Hamadani, Fadya (Iraqi Journal of Pharmaceutical Sciences, 2024)
Inadequate knowledge regarding the appropriate methods for disposing of unused medicines can lead to substantial consequences, such as the accumulation of chemicals and hazardous substances derived from the pharmaceuticals in the surrounding environment. Additionally, for the public's health, pharmacies must be aware of proper methods to eliminate expired medications. The first aim of this study was to evaluate the level of knowledge among community pharmacies regarding the suggested strategies for drug disposal and the potential hazards associated with improper disposal of pharmaceutical waste. Additionally, the study aimed to ascertain the attitudes and practices of community pharmacies toward the appropriate disposal of pharmaceutical waste. The study utilized an observational cross-sectional design, conducted within the timeframe of February 28th to May 11th, 2023. The data were acquired through the implementation of a web-based questionnaire. The study included 385 Iraqi pharmacists. On average, the participants obtained a below-average score of 2.49 out of 8 in the knowledge section. A significant proportion, specifically 91%, of the pharmacists who took part in the study acknowledged employing improper methods for disposing of expired medications within their respective community pharmacies. However, it is worth noting that the majority of these participating pharmacists exhibited a favorable disposition toward recognizing the importance of implementing appropriate disposal practices for expired medication within community pharmacy settings. A significant proportion (86-87%) of the participants exhibit favorable intentions regarding their involvement in the awareness/educational program concerning the tack-back program and the safe disposal of materials. Community-based pharmacies lack expertise and skills regarding drug disposal. However, most pharmacists acknowledge the environmental damage caused by medication disposal. They also showed a willingness to learn about safe medicine disposal. A proper strategy for collecting and disposal of outdated, unused, and expired pharmaceuticals should be implemented.